Grammatical Error Performances in Indonesia EFL Learners’ Writing - Floranti, Astri Dwi; Adiantika, Hanif Nurcholish (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
The present study attempts to investigate the grammatical error performances in Indonesia EFL learners’ writing through the framework of Error Analysis (EA).  The errors are examined and categorized based on the integration of linguistic and surface strategy to gain detailed and comprehensive results. This study was conducted through a qualitative approach within an intrinsic case study design. This study was initiated in 1 senior high school of Kuningan city, West Java. It involved one hundred participants in the twelfth grade. The data were mainly obtained through written test and interview. The results reveal that the learners commit numerous error types in fourteen linguistic categories, especially in the verb areas. The errors are dominated in the form of misinformation and omission type. Furthermore, the possible sources of errors is obtained through the learners’ personal perspectives and analyzing the errors themselves. The sources involves the incapability to accomplish, recognize and comprehend the foreign language rules and its restrictions, less mastery of vocabulary and grammars. Hence, these shortcomings should be great concerns for the involved authorities. It is suggested to consider some advanced actions to overcome the errors and fulfill the learner needs.